Events management services advanced (UAE 3G Elearning FZ LLC, 2016)
"The information in this book consists of competencies that a person must achieve to coordinate events, functions and/or conferences which may be held in conference centers, hotels, motels, restaurants, clubs, resorts and luxury liners. It includes competencies on event planning such as planning and developing an event proposal, concept, and program, selecting a venue and site, and updating event industry knowledge, as well as competencies on on-site event management such as providing onsite management services, managing contractors and updating knowledge on protocol"--Provided by publisher.
Keywords: Special events -- Management; Special management -- Planning